2010
DOI: 10.1128/iai.00539-10
|View full text |Cite
|
Sign up to set email alerts
|

γδ T Cells but Not NK Cells Are Essential for Cell-Mediated Immunity against Plasmodium chabaudi Malaria

Abstract: Blood-stage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
(65 reference statements)
2
32
0
Order By: Relevance
“…On days 14,16,18,20,22 and 24 post-infection (p.i. On days 14,16,18,20,22 and 24 post-infection (p.i.…”
Section: Passive Transfer Of Serummentioning
confidence: 99%
See 1 more Smart Citation
“…On days 14,16,18,20,22 and 24 post-infection (p.i. On days 14,16,18,20,22 and 24 post-infection (p.i.…”
Section: Passive Transfer Of Serummentioning
confidence: 99%
“…5,9,[14][15][16][17][18][19][20] As malaria cd T-cell numbers in peripheral blood and the spleen, cd T cells have been suggested to have a role in malaria. 5,9,[14][15][16][17][18][19][20] As malaria cd T-cell numbers in peripheral blood and the spleen, cd T cells have been suggested to have a role in malaria.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous reports of in vitro and in vivo experiments have suggested that γδ T cells are associated with protective immune responses during malaria infection, the functions of γδ T cells in the spleen remain largely unknown (7579). We recently reported on the mechanism of γδ T-cell-related protective immunity against Plasmodium parasites using the rodent malaria parasite P .…”
Section: Host Immune Responses Of γδ T Cells In Malariamentioning
confidence: 99%
“…Other studies using P . chabaudi parasites have also suggested that γδ T cells are related to, but not essential for, protective immunity against the parasites (76, 78). Thus, this P .…”
Section: Host Immune Responses Of γδ T Cells In Malariamentioning
confidence: 99%
“…50 Similarly, the protective roles of cd-T cells in malaria infection have been confirmed in several independent studies. 51,52 …”
Section: Involvement Of Cd-t Cells In Infectious Diseasesmentioning
confidence: 99%